2020
DOI: 10.14744/phd.2020.03789
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between work-related variables, job satisfaction, and perceived professional autonomy of radiation oncology nurses in Turkey

Abstract: Bu çalışma, Türk radyasyon onkolojisi hemşirelerinin otonomi düzeyi, iş doyumu ve işle ilgili özellikleri arasındaki ilişkiyi ortaya koymak amacıyla yapılmıştır. Gereç ve Yöntem: Bu tanımlayıcı, kesitsel çalışma, üniversite, devlet ve özel hastanelerde görev yapan 138 radyasyon onkolojisi hemşiresinin katılımı ile gerçekleştirilmiştir. Veriler, demografik özellikler ve 30-maddeli Hemşirelik Aktivite Ölçeği'ni içeren soru formu kullanılarak elde edilmiştir. Hemşirelerin mesleki otonomi ve iş doyumu algısı üzeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Similarly, a study conducted in the Philippines, nurse job satisfaction was found to be above the midpoint (Labrague et al., 2020). Studies conducted in Turkey (Durmaz & Sabuncu, 2019; Kılıç et al., 2021; Mert & Türkmen, 2020) and international studies (Bagheri Hossein Abadi et al., 2021; Kim et al., 2017) have also reported that nurses’ job satisfaction was at the medium level. Durmaz and Sabuncu (2019) found intrinsic satisfaction of the nurses higher than extrinsic satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study conducted in the Philippines, nurse job satisfaction was found to be above the midpoint (Labrague et al., 2020). Studies conducted in Turkey (Durmaz & Sabuncu, 2019; Kılıç et al., 2021; Mert & Türkmen, 2020) and international studies (Bagheri Hossein Abadi et al., 2021; Kim et al., 2017) have also reported that nurses’ job satisfaction was at the medium level. Durmaz and Sabuncu (2019) found intrinsic satisfaction of the nurses higher than extrinsic satisfaction.…”
Section: Discussionmentioning
confidence: 99%